(untitled) (Quest Journal of Management and Social Sciences, 2025)
Background: In recent years, many countries, including Nepal have been dealing with continual inflation, largely driven by disruptions in the global supply chain, fluctuations in exchange rates, and domestic structural bottlenecks. As a small open economy with a fixed exchange rate regime and a high dependence on imports, Nepal is particularly vulnerable to external price shocks and policy shifts in its trading partners. At the same time, there is still considerable debate about the extent to which domestic monetary conditions, real sector dynamics, and financial market developments influence Nepal’s inflation pattern, as well as the extent to which structural breaks, such as economic and financial crises, have changed these underlying relationships. Purpose: This study measures the determinants of inflation in Nepal with empirical testing. This paper investigates a critical gap by incorporating a structural break into the ARDL approach, which previous studies have overlooked. Design/methodology/approach: The study incorporates annual time-series data from 1994 to 2024 for Nepal and employs an ARDL model with a structural dummy. Unit root, Chow breakpoint, diagnostic, and Granger causality tests ensure model’s robustness. Findings: The results indicate that there is long-run co-integration among inflation, the exchange rate, and GDP. Exchange rate depreciation significantly drives inflation with a lag, while GDP growth exerts dual effects: short-run moderation but long-run inflationary pressure. Structural breaks have a significant impact on inflationary dynamics, although financial indicators remain insignificant. Conclusions: Nepal’s inflation is simultaneously formed by monetary expansion, fiscal deficit, structural bottlenecks, and exchange rate pass-through. Policy integrity demands inflation targeting, fiscal discipline, and structural reforms to mitigate weakness. Keywords: ARDL Bound Testing, Exchange Rate, Fiscal Deficits, Inflation Dynamics, Structural Break